Unveiling Gendered Chains: A Comparative Case Study of Women’s Political Representation in Thailand and the Philippines - Lagmay, Adley; Soler, Alyssa (Graduate Review of Political Science and Public Administration Journal, 2024)
Thailand and the Philippines exhibit unique challenges for women in public office. Considering the number of women elected in office, the underrepresentation of women in both governments poses a concern. Thus, the main question is, what are the commonalities and differences in women’s political representation in Thailand and the Philippines? To answer the inquiry, this study conducts archival research and employs an Intersectional Feminist framework to shed light on the multifaceted ways in which gender norms intersect with women’s journeys into politics. The objectives of this study are as follows: (1) To analyze the state of women’s political representation including the number of women in elected offices in both countries, (2) to compare and contrast the findings between Thailand and the Philippines to highlight commonalities and differences in women’s political representation, and (3) to examine intersecting identities such as affect women’s political representation. Using the intersectional approach, this paper found that women’s political representation in Thailand and the Philippines is influenced by the inter-relationship of gender, socioeconomic status, and other identities while trying to negotiate space for their inclusion in the practice of politics. With that, this study not only exposes the roots of women’s underrepresentation in politics but also calls for transformative change. It highlights the importance of adopting an Intersectional Feminist perspective to challenge existing norms and advocate for meaningful inclusion of women in decision-making processes.